Pedagogical aspects of the development of leadership qualities in cadets of higher military educational institutions - S. Melnychenko; V. Ovchynnyk; S. Hudal; M. Kulyk (Mukachevo State University, 2024)
The development of leadership qualities in cadets of military institutions is of particular importance in today's conditions, since the formation of a new generation of professional competent officers-leaders will directly affect the combat capability of the Armed Forces and the defence capability of the state as a whole. The purpose of the study was to identify pedagogical aspects and ways to improve the system of leadership development among cadets of the Military Academy. The study analysed the theoretical foundations of the leadership problem and summarized the best Ukrainian and foreign experience. The methods used were: structural-functional method; analysis, induction. The study also used the following methodological approaches: systemic approach; reductionist and holistic approaches. As a result of the research, it was found that the existing system of training military leaders in higher military educational institutions currently has certain significant drawbacks that significantly reduce its effectiveness, namely: insufficient attention is paid to military-humanitarian disciplines, which shape the socio-communicative qualities of a modern leader; outdated reproductive teaching methodologies dominate instead of innovative interactive ones; individual-psychological characteristics of the cadet's personality and potential are not sufficiently taken into account; the educational potential of the faculty is weakly utilized due to mentoring; the system of cadet self-government is underdeveloped, within which future officers could gain real practical leadership experience. Therefore, constructive ways of improving the existing system were proposed by strengthening the humanitarian component of training, wider use of interactive teaching methods, introducing individual educational trajectories, increasing the role of mentoring from senior command staff, creating an effective system of cadet self-government, and substantiating the feasibility of using innovative pedagogical methods of active learning for the effective targeted formation of necessary leadership qualities and competencies. The results of the study on improving the system of leadership development of cadets of Higher Military Educational Institutions are of great practical importance, as they can be used to improve the effectiveness of training officers as future military leaders